Pengaruh Motivasi dan Kepuasan Kerja Terhadap Kinerja Karyawan di Masa Pandemi CoViD-19 - Ghaniiyyu Nafinoor, Gabrielle; Ali Alam, Iskandar (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
The Covid-19 pandemic period had a very bad impact on society and also companies in Indonesia. One of them is an employee at Auto 2000 Way Halim. The decrease in employee work motivation results in a less satisfied sense of working for the employees. In this study we used qualitative and quantitative methods. We collect information using a questionnaire. This study uses a questionnaire as an instrument. With a population of 72 people. The sample is 42 respondents. The object is the employee at the Auto 2000 Sales Operation Way Halim branch. Based on the results of inferential data analysis, the conclusion we get is that motivation and job satisfaction have an influence on the performance of Auto 2000 employees at Way Halim Branch. In this case we can mean that the higher the motivation and job satisfaction, the higher the employee's performance. 1. Employees need high work motivation which must be given by company leaders in order to grow maximum performance in the continuity of working for the company. 2. The existence of a sense of employee satisfaction at work is needed to increase employee performance in the company. Leaders are required to pay more attention to the level of job satisfaction of employees in the future.